2019
DOI: 10.1007/s40291-019-00417-x
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the Role of Biomarkers of Inflammation in the Diagnosis and Management of Complex Regional Pain Syndrome

Abstract: Complex regional pain syndrome (CRPS) is characterized by continuous pain that is often accompanied by sensory, motor, vasomotor, sudomotor, and trophic disturbances. If left untreated, it can have a significant impact on the quality of life of patients. The diagnosis of CRPS is currently based on a set of relatively subjective clinical criteria: the New International Association for the Study of Pain clinical diagnostic criteria for CRPS. There are still no objective laboratory tests to diagnose CRPS and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 83 publications
(147 reference statements)
0
47
0
2
Order By: Relevance
“…So far, objective diagnostic tests to diagnose CRPS are not available. This lack of objective tests hampers early diagnosis and timely initiation of appropriate therapies [ 17 ]. Based on the findings from our previous study in which sIL-2R levels were found to be significantly higher in CRPS patients than in healthy controls [ 8 ], we conducted this current study in which we investigated whether serum sIL-2R could be used to help establish the diagnosis CRPS in patients who were referred to a tertiary referral center with pain in a limb that was suspected to be caused by CRPS.…”
Section: Discussionmentioning
confidence: 99%
“…So far, objective diagnostic tests to diagnose CRPS are not available. This lack of objective tests hampers early diagnosis and timely initiation of appropriate therapies [ 17 ]. Based on the findings from our previous study in which sIL-2R levels were found to be significantly higher in CRPS patients than in healthy controls [ 8 ], we conducted this current study in which we investigated whether serum sIL-2R could be used to help establish the diagnosis CRPS in patients who were referred to a tertiary referral center with pain in a limb that was suspected to be caused by CRPS.…”
Section: Discussionmentioning
confidence: 99%
“…CRPS remains a very difficult condition to treat despite medical advancement [ 11 , 12 ]. The diagnosis of CRPS is purely on clinical grounds as there are no specific diagnostic tests to confirm it [ 13 ]. Our patient demonstrated all the signs and symptoms in all categories of the Orlando diagnostic criteria for CRPS, the Budapest diagnostic criteria of IASP for CRPS and the Japanese CRPS 1 diagnostic criteria for clinical purposes [ 3 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of adrenoreceptors on nociceptive fibers impacts the coupling of sympathetic activation and pain sensitivity in CRPS patients [6]. Validation of biomarkers involved in pathogenesis has the potential to improve diagnostic and remediation approaches by minimizing the subjectivity of current criteria [12].…”
Section: Discussionmentioning
confidence: 99%